Goldenhar's Syndrome (Oculo-Auriculo-Vertebral Dysplasia) - N. K. Mehdiratta; D. R. Singh; P. C. Misra; S. K. Singh (Indian Journal of Plastic Surgery)
Oculo-auriculo-vertebral syndrome (Goldenhar's syndrome) was found in two cases, who had epibulbar dermoids, pre-auricular skin tags and hypomandibulosis. One case also had left sided complete congenital inguinal hernia.